2006
DOI: 10.1210/jc.2005-1616
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Pituitary Irradiation Is Effective in Lowering Serum Growth Hormone and Insulin-Like Growth Factor-I in Patients with Acromegaly

Abstract: In this, the largest series reported, conventional pituitary irradiation is shown to be an effective and safe means of reducing both serum GH and IGF-I concentrations in patients with acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
102
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(126 citation statements)
references
References 39 publications
15
102
2
4
Order By: Relevance
“…A recent report of the UK National Acromegaly Register Study Group has also demonstrated that significant numbers of patients have normal IGF1 levels after irradiation though in that series the length of time off adjunctive treatment was not specified (18). Our results are complimentary to these and have the advantage of being in one centre with a single laboratory, clinic and radiation site, albeit with two irradiation schedules and three IGF1 assays over the 40 years.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A recent report of the UK National Acromegaly Register Study Group has also demonstrated that significant numbers of patients have normal IGF1 levels after irradiation though in that series the length of time off adjunctive treatment was not specified (18). Our results are complimentary to these and have the advantage of being in one centre with a single laboratory, clinic and radiation site, albeit with two irradiation schedules and three IGF1 assays over the 40 years.…”
Section: Discussionsupporting
confidence: 63%
“…The effect of EPI in normalising serum IGF1 levels has been a cause of dispute (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)30) (Table 1). Barkan et al reported that following radiotherapy for acromegaly only 2 out of 38 patients (5%) taken off medical therapy for 2-3 weeks normalized IGF1 over 10 years despite attenuation of GH levels (14).…”
Section: Introductionmentioning
confidence: 99%
“…RT is effective in lowering serum GH and IGF1 concentrations in patients with acromegaly, with biochemical control of the disease being achieved in 60% of patients within 10 years after irradiation (3).…”
Section: Introductionmentioning
confidence: 99%
“…In humans suffering from acromegaly, IGF‐1 concentrations attenuate very slowly after RT and maximal control of the release of GH may require more than 15 years. Radiotherapy is therefore generally reserved for tumors that have recurred or persisted after surgery 21. On the other hand, successful hypophysectomy leads to an immediate reduction in GH and IGF‐1 and both parameters are therefore used to assess biochemical control of disease, as well as predict the risk of recurrence 22.…”
Section: Discussionmentioning
confidence: 99%